Ab initio study of metal carbide hydrides in the 2.25Cr1Mo0.25V steel. Issue 9 (24th February 2021) - He, Min; Onwudinanti, Chidozie; Zheng, Yaoting; Wu, Xiaomei; Zhang, Zaoxiao; Tao, Shuxia
Abstract : 2.25Cr1Mo0.25V is a state-of the-art alloy used in the fabrication of modern hydrogenation reactors. Abstract : 2.25Cr1Mo0.25V is a state-of the-art alloy used in the fabrication of modern hydrogenation reactors. Compared to the conventional 2.25Cr1Mo steel, the 2.25Cr1Mo0.25V steel exhibits a better performance, in particular higher hydrogen damage resistance. Previous experimental studies indicate that carbides in steels may be responsible for the hydrogen-induced damage. To gain a better understanding of the mechanism of such damage, it is essential to study hydrogen uptake in metal carbides. In this study, Density Functional Theory (DFT) is used to investigate the stability of chromium, molybdenum and vanadium carbides (CrxCy, MoxCy and VxCy) in the 2.25Cr1Mo0.25V steel. The stability of their corresponding interstitial hydrides was also explored. The results showed that Cr7 C3, Mo2 C and V6 C5 are the most stable carbides in their respective metal–carbon (Cr–C, Mo–C and V–C) binary systems. Specifically, V6 C5 shows the strongest hydrogen absorption ability because of its strong V–H and C–H ionic bonds. On the other hand, V4 C3, whose presence in the alloy was established in experimental studies, is predicted to be stable as well, along with V6 C5 . Our findings indicate that the hydrogen absorption ability of V4 C3 is higher than that of V6 C5 . Additionally, the charge and chemical bonding analyses reveal that the stability of the metal carbide hydrides strongly depends on the electronegativity of the metal. Due to the high electronegativity of V, vanadium carbides form the strongest ionic bonds with hydrogen, compared to those of Mo and Cr. The results from this study suggest that the unique capacity of accommodating hydrogen in the vanadium carbides plays an important role in improved hydrogen damage resistance of the 2.25Cr1Mo0.25V alloy in hydrogenation reactors.